Less shared decision-making in consultations with lower health literate cancer patients: an observational mixed-methods study - Merel D. van Eick; Maartje Binnendijk; Hanneke W. M. van Laarhoven; Ellen M. A. Smets; Danielle R. M. Timmermans; Mark I. van Berge Henegouwen; Marijke Melles; Olga C. Damman (Health Literacy and Communication Open)
Background Shared decision-making (SDM) is now widely utilized in treatment decision-making for complex medical conditions like esophagogastric cancer. However, patients with lower health literacy (HL) levels often face greater challenges in participating in SDM compared to those with higher HL levels.Aim To investigate the use of SDM in relation to patient HL in consultations on esophagogastric cancer treatment.Methods This was an explorative study employing both quantitative and qualitative analysis of data from audio-recorded treatment consultations (N = 38) with esophagogastric cancer patients (N = 11 lower HL, N = 7 higher HL). HL was primarily measured with the Newest Vital Sign-Dutch. The Observing Patient Involvement in Shared Decision-making (OPTION)-12-scale and qualitative thematic analysis were applied. Total OPTION-scores ranged from 0 (behavior not observed) to 100 (behavior exhibited to a very high standard).Results OPTION-12 scores for consultations with lower HL patients were consistently lower, with a significant difference for the total OPTION scores (lower HL: M = 24.25, higher HL: M = 40.25, p < 0.001). Furthermore, the following sub-scores indicated significant differences between consultations with lower and higher HL patients: drawing attention to the problem (p = 0.018), exploring the patient’s expectations and preferred level of involvement (p = 0.023), providing opportunity to ask questions (p = 0.037), and indicating the need to make and review the decision (p = < 0.001, and p = 0.002). Thematic analysis showed that lower HL patients asked less actively for clarification of treatment and that they followed treatment advice from clinicians more frequently. The use of plain language and supportive tools—seen as HL-sensitive communication strategies—was observed mainly in consultations with higher HL patients.Discussion Lower HL patients were involved less in SDM by their clinician, especially in the phases of discussing patient values, expectations, and preferences. Furthermore, clinicians used limited plain language and supportive tools in consultations with lower HL patients. This highlights a need for tailored communication strategies to ensure equitable engagement in SDM. The current study is preliminary work that needs further exploration, for example, in larger samples and with assessors blind to patient HL levels.